Ekplorasi Pengaruh Warna Terhadap Perkembangan Psikologi dan Mental Anak di SDN Kalirungkut 1 Surabaya - Mourin, Lourenzo; Gunta, Arkadewa Bumisyach; Naafi’, Ma’rifatul Ilmin; Maharani, Alia Putri ,; Pratama, Alvian Rizky; Nurhayati, Eni (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
In the world of architecture, choosing a wall color is one of the important things that will affect the style and function of the building itself. Color helps create visual balance and form an atmosphere that is appropriate for its environment. For example, bright yellow in a room can stimulate its occupants to be more creative and attractive. In contrast to a room painted black, it will give an impression of sadness. Therefore, the presence of color can give a different impression to each room. The method used in this study was qualitative observation and interviews to determine the emotional sensitivity of students at SDN Kalirungkut 1 Surabaya. The results of this study indicate that more elementary school students choose bright colors than dark colors. This can be caused by several factors, such as visual, psychological, social, and cultural aspects. This study highlights the importance of the role of color in creating a learning environment that supports students' comfort and creativity. Therefore, the selection of colors in learning spaces should consider the psychological impact they generate.